Canal de crédito para o Brasil : uma avaliação empírica - Bogado, Pedro Rangel (2011)
The identification problem of supply and demand equations for testing the bank lending channel has been discussed in recent decades. This work evaluates the identification strategy carried out in a VECM setting to determine if there is empirical evidence of a bank lending channel in the transmission of monetary policy in Brazil. Monthly aggregate data was used for the period 2001 through 2010.